2014
DOI: 10.1007/s13277-014-2258-5
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of perineural invasion of gastric carcinoma into the 7th edition tumor–node–metastasis staging system

Abstract: The aim of this study was to determine the prognostic value of perineural invasion (PNI) in patients with gastric cancer who underwent curative resection. We retrospectively analyzed 518 patients who had undergone curative gastrectomy. Paraffin sections of surgical specimens from all patients were stained with hematoxylin and eosin. PNI was defined when carcinoma cells infiltrated into the perineurium or neural fascicles. Patients with PNI had a significantly larger tumors (≥5.0 cm), lymphatic venous invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…This is an important pathway for the local spread of cancer cells, which represented an aggressive biological behaviour of tumours 5. According to the previous reports, the prevalence of PNI in GC patients varied from 31.7% to 65.0% 6–9. Positive PNI was not infrequent in surgically resected specimens of GC patients with the improvement of detection technology and pathologists’ experience.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is an important pathway for the local spread of cancer cells, which represented an aggressive biological behaviour of tumours 5. According to the previous reports, the prevalence of PNI in GC patients varied from 31.7% to 65.0% 6–9. Positive PNI was not infrequent in surgically resected specimens of GC patients with the improvement of detection technology and pathologists’ experience.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, there have been several studies evaluating the prognostic significance of PNI for GC patients, but the results were conflicting. Some studies regarded PNI as a useful prognostic factor for GC patients who underwent curative resection,7 8 15 but others reported that it could not provide more additional prognostic information than well-known clinicopathological factors such as tumour, node, metastases (TNM) stage and differentiation type 9 16. In view of no consensus on this topic, more research evidence need to be provided to help us better understand the prognostic significance of PNI and guide individual treatment for GC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 28 in a group of patients who underwent radical resection for gastric carcinoma found that the presence on PNI had a significant correlation with size of tumor (R5 cm), lymphatic venous invasion, deeper tumor invasion (T4), lymph node metastases (N3), and deeper TNM stage (III), which were proved to be associated with worse survival outcomes. In the multivariate analysis, presence of PNI and classical oncologic variables maintained significance and was recognized as an independent prognostic factor in gastric carcinoma patients with poor survival.…”
Section: Commentsmentioning
confidence: 99%
“…These 2 important prognostic factors are currently used for stratifying patients to decide the best treatment strategy. Jiang et al 28 incorporated PNI into N3 and TNM stage III in patients with gastric carcinoma through the redefinition of stage III in III PNI and N stage in N PNI . Their under-categorization reached a lower 22 log-likelihood value and a higher hazard ratio and 95% confidence interval, which represented an optimum prognostic stratification, together with better homogeneity, and discriminatory ability.…”
Section: Commentsmentioning
confidence: 99%
“…In a previous study on gastric cancer, PNI emerged as an independent prognostic factor for survival. Additionally, the proportion of PNI positivity increased with progression and clinical stage of disease; therefore, it was suggested to incorporate this into tumor, node, metastasis staging (8). In another previous study on pancreatic cancer, PNI was considered as an independent predictor of prognosis and was associated with neuropathic pain (9).…”
Section: Introductionmentioning
confidence: 99%